ASSOCIATION BETWEEN MATERNAL SERUM LIPID PROFILE AT LATE GESTATION WITH NEONATAL MACROSOMIA - Nasir, Salama Kamel; Khaleel, Rawaa Mahfoudh; Abdullah, Naz Azad (Journal of Sulaimani Medical College, 2022)
Background Macrosomia is a serious health problem that is highly prevalent and can negatively affect neonatal and maternal outcomes. Pregnant women and neonates can be negatively influenced by dyslipidemia (high maternal serum lipids) which also results in the development of fetal macrosomia.. Objectives The current study aimed to determine how maternal lipid profile during the third trimester of pregnancy correlated with fetal birthweight. Patients and Methods A prospective cohort study was conducted in Sulaimani Maternity Teaching Hospital over eight months, starting from the 1st of September 2018 till the 30th of April 2019. The study included 123 pregnant with a viable singleton pregnancy, gestational age > 32 weeks, delivered between 37 and 42 weeks of gestational age, and women suffering from thyroid disorders and hypertension. For all women, total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), and serum triglycerides (TG) were measured. In addition, the women were followed up until their childbirth, and the correlation between the mothers’ lipid profile and their neonates’ weight was measured.. Results The mean age ± SD (standard deviation) of the studied women was 31.10± 3.65 years, ranging from (25 to 38) years. Regarding their parity, 78% of women were multiparous (have 2-4 children), and the remaining (22%) were primipara. Among the 123 participating women, 23 (18.7%) delivered macrosomic babies (weight > 4kg), and 100 (81.3%) delivered babies with normal birth weight. Fifteen women (12.2%) have high cholesterol levels, and all delivered macrosomic newborns, with a statistically significant association (P=0.001) between macrosomia and maternal cholesterol level. Also, the prevalence of macrosomia was significantly higher among women with high serum triglyceride levels (P=0.001). Conclusion There is a significant association between increased risk of macrosomia and high serum cholesterol and triglycerides levels during pregnancy.
Keywords: macrosomia; lipid profile; dyslipidemia; pregnancy